Inactivation status of PCDH11X: sexual dimorphisms in gene expression levels in brain. - Lopes, A; Ross, N; Close, J; Dagnall, A; Amorim, A; Crow, T (2006)
Genes escaping X-inactivation are predicted to contribute to differences in gene dosage between the sexes and are the prime candidates for being involved in the phenotype observed in individuals with X chromosome aneuploidies. Of particular interest is ProtocadherinX (PCDH11X or PCDHX), a recently described gene expressed in brain. In humans, PCDH11X has a homologue on the Y chromosome and is predicted to escape from X-inactivation. Employing bisulphite sequencing analysis we found absence of CpG island methylation on both the active and the inactive X chromosomes, providing a strong indication that PCDH11X escapes inactivation in humans. Furthermore, a sexual dimorphism in levels of expression in brain tissue was observed by quantitative real-time PCR, with females presenting an up to 2-fold excess in the abundance of PCDH11X transcripts. We relate these findings to sexually dimorphic traits in the human brain. Interestingly, PCDH11X/Y gene pair is unique to Homo sapiens, since the X-linked gene was transposed to the Y chromosome after the human-chimpanzee lineages split. Although no differences in promoter methylation were found between humans and chimpanzees, evidence of an upregulation of PCDH11X in humans deserves further investigation.